Anisotropic Diffusion of Microbeads Surrounded by an Anisotropically Elongated Supramolecular Diarylethene Architecture under Linearly Polarized Light. Issue 11 (31st October 2017) - Sakaguchi, Akira; Higashiguchi, Kenji; Matsuda, Kenji
Abstract: The front cover artwork is provided by the group of Prof. K. Matsuda at Kyoto University (Japan).The image shows the anisotropically elongated diarylethene fibre structure generated by linearly polarized light and the anisotropic diffusion of microbeads surrounded by the anisotropically elongated fibres. Read the full text of the Communication at10.1002/cptc.201700101 . Abstract : "Self‐assembled microstructures of an amphiphilic diarylethene featuring an alkyl chain and triethylene glycol groups were found to show a photo‐induced reversible morphological change…" This and more about the story behind the front cover can be found in the Communication at10.1002/cptc.201700101 .